Bersyukur itu menyenangkan : panduan anak agar selalu bersyukur dan berterima kasih / Michaclene Mundy ; ilustrator, R.W. Alley ; penerjemah, Flora Maharani, Natan Arya - MUNDY, Michaclene; Aley, R.W.; Flora Maharani; Natan Arya (Kanisius, 2015)
[30] hlm. : ilus. ; 21 cm.